2016
DOI: 10.1080/01446193.2016.1162316
|View full text |Cite
|
Sign up to set email alerts
|

Detecting defects in the UK new-build housing sector: a learning perspective

Abstract: Rapid growth in the production of new homes in the UK is putting build quality under pressure as evidenced by an increase in the number of defects. Housing associations (HAs) contribute approximately 20% of the UK's new housing supply. HAs are currently experiencing central government funding cuts and rental revenue reductions. As part of HAs' quest to ramp up supply despite tight budget conditions, they are reviewing how they learn from defects. Learning from defects is argued as a means of reducing the persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Finally, this research can complement existing defect scholarship to help researchers identify what types of defects are important (based upon the level of disruption they cause and H&S concerns they pose) and subsequently which defects should be focussed on. Further, research into house builders' (HBs') defect reduction attempts in practice found that they sought to reduce the highest frequency defect types experiencedalbeit with limited success (Hopkin et al, 2016). The findings from this research could offer the HBs an alternative approach to determine which defects should be targeted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, this research can complement existing defect scholarship to help researchers identify what types of defects are important (based upon the level of disruption they cause and H&S concerns they pose) and subsequently which defects should be focussed on. Further, research into house builders' (HBs') defect reduction attempts in practice found that they sought to reduce the highest frequency defect types experiencedalbeit with limited success (Hopkin et al, 2016). The findings from this research could offer the HBs an alternative approach to determine which defects should be targeted.…”
Section: Discussionmentioning
confidence: 97%
“…House builders (HBs) have responded to the pent up demand and policy incentives by significantly up-scaling supply, with a 78 per cent increase in housing starts for 2015 compared to the 2008 downturn (Department for Communities and Local Government, 2016). There is evidence that the rapid up-scaling of supply has had a negative impact on build quality, causing an increase in defects (Hopkin et al, 2016). There is strong historical evidence that a step-change in housing production causes supply chains and skills to become over-stretched due to excessive workload (Sommerville et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…By this, they mean that even before occupants move into their new homes, they have numerous defects. This issue is a global problem; in fact, research on defects in the residential building has been conducted in many countries (Shirkavand et al, 2016;Hopkin et al, 2016;Chong and Low, 2005;Christudason, 2007;Abdul-Rahman et al, 2014 andRotimi, et al, 2015). The inadequacies of affordable housing supply are known to the Malaysian Government, and to curtail the housing shortage, many schemes, incentives, programs, and interventions have been introduced.…”
Section: Background and Conceptual Justificationmentioning
confidence: 99%
“…To address this issue, they proposed measures such as improving the management during the DLP as well as improving the procedures through the cooperation of contractors, consultants, and customers [12]. Hopkin et al (2016) surveyed UK major stakeholders in regard to the defect frequency to determine the most important types of defects and to identify which defects must be focused on after defects have occurred [32]. However, there are differences in the perspectives about defects that occur during DLP among the major stakeholders that were analyzed [9].…”
Section: Literature Reviewmentioning
confidence: 99%